Kinetics of Degradation of Metribuzin in aqueous solution using Zero Valent Iron Nanoparticles - K’Owino, Isaac O.; Okello, Veronica; Masika, Kevin (My University, 2018)
In this work, zero-valent iron nanoparticles (nZVI NPs) were synthesized in (EW-Fe0) ethanol -water mixed system and have been evaluated for degradation in aqueous solution of metribuzin. The batch experiments at varying solution pH showed the degradation efficiency of 93.22%, 83.74% and 70.09% for the pH value 10, 7 and 4 respectively. Application of the varying dosage; (2% Feo w/v, 4% Feo w/v, 6% Feo w/v) reflected an increasing trend as per the recorded degradation efficiency of 54.36 %, 67.28% and 79.38% respectively. Scanning electron microscopy (SEM) and Energy Dispersive X-ray Analysis (EDXA) were used to determine surface morphology and crystallinity of the particles respectively. The batch kinetic tests gave kinetics of a pseudo-first order along with the rate constants, Kobs of 0.2659 h-1, 0.2320 h-1 and 0.2066 h-1 after incubating 6% Feo w/v with 10 ppm, 15 ppm and 20 ppm of Metribuzin respectively. The residual metribuzin was monitored in the solution by using of high performance liquid chromatography (HPLC) and UV Spectrophotometer. Thus, we present nZVI as an alternative rapid method for the detoxification of metribuzin.
Keywords: Metribuzin; Degradation; Zero Valent Iron Nanoparticles; pseudo-first order